1998
DOI: 10.1177/003693309804300207
|View full text |Cite
|
Sign up to set email alerts
|

Domiciliary Nebuliser Therapy — A Valuable Option in Chronic Asthma and Chronic Obstructive Pulmonary Disease?

Abstract: Domiciliary nebulisers are in widespread use for patients who have severe chronic airways disease, both asthma and chronic obstructive pulmonary disease (COPD). We report a study of the use of domiciliary nebulisers designed to assess practical problems and the value of such therapy in preventing hospital admissions. A total of 405 patients underwent a structured interview at home and their case records were reviewed. Technical performance of the nebuliser compressors was assessed. The mean (SD) age of those i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 15 17 18 Blockage of inlet filters and lack of servicing affect compressor performance. 14 In this study, discoloured filters were observed and a lack of servicing of the compressor was especially prominent.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“… 15 17 18 Blockage of inlet filters and lack of servicing affect compressor performance. 14 In this study, discoloured filters were observed and a lack of servicing of the compressor was especially prominent.…”
Section: Discussionmentioning
confidence: 56%
“…In the few studies investigating nebuliser use by patients with COPD in the home, problems have been reported with assembling nebuliser equipment 13 and gauging how long to nebulise fluids. 14 Inadequate cleaning of equipment after use has been highlighted in several studies. 13–18 While a number of problems have been identified, a comprehensive study of home nebuliser use, from the perspectives of patients with COPD, to identify potential contributory factors that may lead to treatment failure, has not been undertaken.…”
Section: Introductionmentioning
confidence: 99%